France before 1789 : the unraveling of an absolutist regime - Elster, Jon, 1940- (Princeton University Press, 2020)
"France before 1789 presents the main features of the prodigiously complex social system of the ancien regime which proceeded the French Revolution. In doing so Jon Elster goes beyond formal institutions to show how they worked in practice. He draws on a host of examples and contemporary texts to illuminate the perverse and sometimes pathological effects of this system and seeks to provide a detailed analysis of the political institutions that undergirded it. Whereas Tocqueville, in his famous analysis of the ancient regime, wanted to understand the old regime as a prelude to revolution, Elster views it as a prelude to constitution-making prompted by and intended to resolve these perversities. He views these as overlapping, yet important enough to render distinct. In addition to defending a particular set of substantive propositions about the conditions which led to the Constituent Assembly, Elster argues for a specific methodological approach to history, which emphasizes supplementing the historian's craft with approaches from the social sciences. Ultimately, he does not claim to answer the historians' questions better than they do. But he does aspire to ask and sometimes answer questions that historians have not formulated in order to better understand one of the most significant examples of collective decision-making history offers us"--